Implementasi Sikap Bela Negara dalam Menyambut Pemilu 2024: Perspektif dan Tantangan bagi Warga Negara Indonesia: Implementing a Sense of National Duty in Preparation for the 2024 Elections: Perspectives and Challenges for Indonesian Citizens - Tomi Khoyron Nasir; Ruli Agustin; Irwan Triadi (SIYASI: Jurnal Trias Politica, 2024)
In relation to the ongoing stages of the 2024 General Election contestation in Indonesia, the level of national defense awareness among Indonesian citizens has begun to fade, resulting in negative fanaticism and fragmented community groups. The emergence of excessive fanaticism among the Indonesian people has led to many new conflicts, such as the proliferation of hoax news, divisive politics, fictitious campaigns, black campaigns, defamation, hate speech, and SARA-based politics (ethnicity, religion, race, and intergroup relations), which seriously disrupt the public order of Indonesian society. Therefore, this research will discuss the behavioral patterns of Indonesian citizens in facing the 2024 General Election, as well as examine the Indonesian government's efforts to address the declining spirit of national defense in confronting the 2024 General Election. The research method used by the author is a normative juridical method, which involves collecting various data information from secondary sources, such as books, legal products and legislation, e-books, scientific journals, and previous research. With the various efforts of the Indonesian government to enhance and maintain the spirit of national defense among the Indonesian people in participating in the 2024 General Election, it is expected that the 2024 General Election will produce elected leaders who demonstrate high national integrity and national defense behavior based on the satisfaction of the majority of their constituents.